Leveraging On Generative Artificial Intelligence Tools in Enhancing Teaching, Research and Assessment of Learning in Nigerian Tertiary Institutions - Usman, Abubakar; Bello, Adamu; Aliyu, Amina Aji; Adamu , Alkali Usman (Kashere Journal of Education, 2025)
This paper examined how Nigerian tertiary institutions can leverage GenAI to enhance teaching, research, and assessment while attending to ethical, infrastructural and pedagogical safeguards. Drawing on recent empirical studies and policy analyses, the study offers evidenceinformed recommendations for responsible and contextually appropriate implementation that promotes quality, equity, and academic integrity. Generative Artificial Intelligence (GenAI) is reshaping teaching, research, and assessment in tertiary education, offering transformative opportunities for improving pedagogy, scholarly productivity, and learning evaluation. In Nigerian higher institutions, where challenges such as high student–staff ratio, limited learning resources, and inadequate research infrastructure persist, GenAI provides scalable solutions that enhance instructional delivery and academic efficiency. In teaching, GenAI supports educators by automating routine tasks, generating personalised learning materials, and offering timely, detailed feedback that strengthens student engagement and self-regulated learning. As a research tool, GenAI accelerates literature discovery, facilitates synthesis, support methodological design nd streamline qualitative and quantitative analysis, although human oversight remains essential to ensure accuracy and research integrity. In assessment, GenAI enables automated scoring, item generation, and consistent feedback while emerging frameworks such as the AI Assessment Scale (AIAS) demonstrate its potential to improve learning outcomes and reduce academic misconduct. However, concerns regarding fairness, transparency, data privacy nd academic integrity underscore the need for strong institutional policies and ethical governance. Collectively, GenAI offers significant potential to transform Nigerian tertiary education when thoughtfully and responsibly integrated.